2016
DOI: 10.3390/en9060407
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Spatial Heterogeneity of Individual Preferences for Ambient Heating Systems

Abstract: Abstract:The estimation and policy use of spatially explicit discrete choice models has yet to receive serious attention from practitioners. In this study we aim to analyze how geographical variables influence individuals' sensitivity to key features of heating systems, namely investment cost and CO 2 emissions. This is of particular policy interest as heating systems are strongly connected to two major current environmental issues: emissions of pollutants and increased use of renewable resources. We estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Consumers might, for example, be more willing to accept a control of their washing machine than of their freezer. Third, we analyze if consumers show dominant decision-making behavior, i.e., decision strategies, by analyzing individual WTA values using individual-level parameter estimates as for example performed by Greene et al [20] or Franceschinis et al [21]. We expect, for example, to identify respondents who will never choose a TOU tariff, regardless of a discount, because of their perceived discomfort.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers might, for example, be more willing to accept a control of their washing machine than of their freezer. Third, we analyze if consumers show dominant decision-making behavior, i.e., decision strategies, by analyzing individual WTA values using individual-level parameter estimates as for example performed by Greene et al [20] or Franceschinis et al [21]. We expect, for example, to identify respondents who will never choose a TOU tariff, regardless of a discount, because of their perceived discomfort.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies analyse awareness [12,13] and estimate citizens' willingness to pay (WTP) for the use of renewable energy sources (e.g., [14][15][16][17][18][19][20]). A number of studies also investigate homeowners' preferences for renewable domestic heating systems using the discrete choice experiment (DCE) approach [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] or conjoint and variance analysis [36], and most of them suggest that whilst renewable energy adoption is notably valued by households, this value is not enough to counterbalance the importance of the economic factors while purchasing a new heating [24,25,27,29].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has identified a variety of factors fostering and/or hindering the adoption process and identified variables influencing environmentally significant decision-making [29]. Diffusion of innovation and technology acceptance [6][7][8][9]12,14,[30][31][32], willingness to pay, spending motivation, and new business models, such as contracting and leasing [11,[15][16][17][33][34][35][36][37][38][39], diverse household preferences on renovation [33,40], sociodemographic factors [29,35,40], barriers of adoption [12,35,41], etc., are only some examples of the existing approaches. Furthermore, there are several theories or models relating to decision-making and energy use in dwellings.…”
Section: Literature Overviewmentioning
confidence: 99%